Factors influencing the economics of public charging infrastructures for EV – A review. (October 2018) - Zhang, Qi; Li, Hailong; Zhu, Lijing; Campana, Pietro Elia; Lu, Huihui; Wallin, Fredrik; Sun, Qie
Abstract: Growing concerns about energy conservation and the environmental impacts of greenhouse gas emissions over the world have promoted the development of the electric vehicles (EVs) market. However, one of the biggest barriers in the development of the EV market is the lack of the public charging infrastructure. This paper reviews the factors that can directly and indirectly influence the economics of the public charging infrastructure. The knowledge gaps, barriers and opportunities in the development of the charging infrastructure have been identified and analyzed. In order to promote the development of the public charging infrastructure, more research efforts should be paid on the impacts of psychological factors of customers and the technical development of charging infrastructures and EV batteries. The government support has been proved to play an important role, so that how the government policy can be tailored for the development of the charging infrastructure market should receive more attentions. In addition, the charging price as an endogenous factor should be considered more carefully in modelling the charging infrastructure market. New business models are also urgently needed to accelerate the future development of the public charging infrastructure. Highlights: This paper reviews the factors that can influence the economics of public charging infrastructures. Knowledge gaps, barriers and opportunities in the development of charging infrastructures have been identified. More research efforts should be focused on customer psychological factors. The government policy should be tailored according to the status of charging infrastructure market. Developing new business models of charging infrastructures should receive more attention.